Hodophilus pseudoglabripes (Clavariaceae, Agaricales), a new species from Thailand - Tang, Songming; Lv, Tong; He, Jun; Yu, Fengming; Luo, Hongmei; Li, Shuhong (Phytotaxa, 2023)
Hodophilus pseudoglabripes, a new species with a strong earthy odor, was found in forests dominated by Castanopsis (Fagaceae) in northern Thailand. This species is introduced with microscopic and macroscopic descriptions and colour photographs. Phylogenetic affinities were determined based on a combination of internal transcribed spacers (ITS) and large subunit (nrLSU) of the nuclear ribosomal DNA (rDNA). The new species was placed in Hodophilus, within an independent clade comprising the other two species from Asia, H. glabripes and H. indicus. This is the first report of the genus Hodophilus in Thailand. An updated key to all members of the genus Hodophilus is also provided.